Liquid Chromatographic Determination of NSAIDs in Urine After Dispersive Liquid-Liquid Microextraction Based on Solidification of Floating Organic Droplets - Dyia Syaleyana, Md. Shukri (2015)
An environmentally benign method of sample preparation based on dispersive liquid–liquid microextraction and solidification of floating organic droplets (DLLME-SFO) coupled with high-performance liquid chromatography with ultraviolet detection has been developed for analysis of non-steroidal anti-inflammatory drugs (NSAIDs) in biological fluids. A low-toxicity solvent was used to replace the chlorinated solvents commonly used in conventional DLLME. Seven conditions were investigated and optimized: type and volume of extraction solvent and dispersive solvent, extraction time, effect of addition of salt, and sample pH. Under the optimum conditions, good linearity was obtained in the range 0.01–10 µg mL−1, with coefficients of determination (r2) >0.9949. Detection limits were in the range 0.0034–0.0052 µg mL−1 with good reproducibility (RSD) and satisfactory inter-day and intra-day recovery (95.7–115.6 %). The method was successfully used for analysis of diclofenac, mefenamic acid, and ketoprofen in human urine. Analysis of urine samples from a patient 2 and 4 h after administration of diclofenac revealed concentrations of 1.20 and 0.34 µg mL−1, respectively.